Dealing With Paradoxes, Manufacturing Governance: Organizational Change in European Third-Sector Organizations. (April 2022) - Petrella, Francesca; Simsa, Ruth; Pape, Ulla; Pahl, Joachim Benedikt; Brandsen, Taco; Richez-Battesti, Nadine; Zimmer, Annette
Third-sector organizations (TSOs) in Europe have been confronted with profound changes to their regulatory and societal environments. By applying the concepts of "organizational paradoxes" and "governance, " we analyze how TSOs have adjusted their governance as a response to these environmental challenges. Based on organizational case studies in France, Germany, and the Netherlands, we argue that TSOs have found multiple ways to address tensions at the organizational level, for example, by mobilizing and combining resources, re-arranging their organizational governance and by adopting new legal forms. These changes have resulted in hybridization and increased organizational complexity that might translate into the emergence of new paradoxes at the organizational level. Therefore, dealing with paradoxes constitutes an ongoing process for TSOs that goes beyond incremental adjustments.